Meningkatkan Kepuasan Konsumen melalui Consumer Taste Perception terhadap Keputusan Pembelian Ulang pada UMKM Kuliner di Kota Bandung - Hadiantini, Ratih; Sarifiyono, Aggi Panigoro; Maharani, Hani (Jurnal Maksipreneur, 2023)
The recovery of culinary MSMEs (Micro, Small, and Medium Enterprises) due to the pandemic is still in the process of moving towards stability. Many MSMEs in Bandung, especially in the culinary sector, have experienced a decline in their business turnover. This research aims to analyze efforts to increase purchase satisfaction in the culinary sector in the city of Bandung based on consumer taste perceptions of purchase satisfaction which have an impact on repeat purchase decisions. The results of this research prove that consumer taste perception has a significant effect on purchase satisfaction. Apart from that, consumer taste perception has quite an influence on repurchase decisions, while purchase satisfaction has a significant influence on repurchase decisions. Consumer taste perception was found to have an indirect influence on purchasing decisions through purchase satisfaction. Overall, the results of this research indicate that consumer taste perception is able to influence repurchase decisions, both directly and indirectly through purchase satisfaction.